(3eNJUQ TQM Gdedhi Ydi GdSeQbfOis - (3Gdedhis; (3GdeLjQj , TgGH GdOjf CHh GdYHGS CMeO Hf YHO GdaJGM Hf jhSa Hf YeQ Gdedhj GdTGaYj,J (B1181 (3g` s
(3ChdgG (B:s
(3CeG HYO abO cfJ TQMJ QSGdg GdEeGe GdSeQbfOi ai GdGSJYGQGJ s
(3BNQgG (B:s
(3ajLYd TGci GdSdGM bQjfI hGddg CYde s
(3Vef eLehY s
(3YdjgG Jedcs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B152 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B278s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs